Population Dynamics of Dalbergia sissoo Defoliators , Plecoptera reflexa and Dichomeris eridantis - Prasad, Lalji; Pandey, Rajiv; Ansari, Israr A.; Chandra, Subhash (Indian Forester, 2002)
The cyclic pattern in the population dynamics of defoliators D. eridantis and P. reflexa of Dalbergia sissoo is governed by delayed density-dependent factors and its growth rate. However , environmental variable particularly humidity and temperature are also influencing the population , since theses are directly affecting the parasitism phenomenon.